Studies on post-partum anestrous in cattle - Araújo, Paulo Graça; Pizelli, Gelio Nogueira; Carvalho, Mauro Ribeiro de; Resende, Osvaldo de Almeida; Britto, Dirce P.P. de Souza (Pesquisa Agropecuaria Brasileira, 2014)
Twenty dairy herds, for a total of 4,267 animals of which 2,500 were in lactation, located in the Vale do Paraíba, the states of Rio de Janeiro and São Paulo, were used in these studies. Rectal palpations of 1,065 cows which had not shown signs of heat for more than five months, revealed true anestrous in 750 (17.5%) with the majority of these (70.4%) showing “smooth” ovaries. A total of six experiments were conducted. With the hormone levels used, Estrogen, PMS of HCG did not significantly increase ovulation or pregnancy when compared with the untreated controls. The same was true for ovarian massage compared with the controls.